Predictors of short birth interval among women of reproductive age attending the young child clinic at a tertiary hospital in Western Uganda: a cross-section study - Elioba, John L. R.; Hakizimana, Theoneste; Atuhaire, Shallon; Ishimwe, Marie P. S.; Naranjo, Ubarnel A.; Ramirez, Fernando P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Short birth interval continues to increase in sub-Sahara Africa of which Uganda is part. If all birth-to-pregnancy intervals were spaced at least 2 years apart as recommended by the world health organization, most under-five deaths would be avoided. We aim at determining the predictors of short birth interval among women of reproductive age at tertiary hospitals, Uganda. Methods: A cross-sectional study involving 325 women of reproductive age attending the young child clinic at Fortportal Regional Referral Hospital was conducted from July 2022 to October 2022. Interviewer-administered questionnaires were used to obtain data used for analysis. Descriptive statistics followed by binary logistic regression were conducted to achieve the study objectives using SPSS version 22.0. Results: Out of 325 participants, 94 (29%) had short birth interval. Maternal age (OR=3.4, 95% CI: 1.15-10.13; p=0.02), no previous pregnancy planning (OR=3.4, 95% CI: 1.23-9.41; p=0.01), duration of breastfeeding less than 12 months (OR=1.9, 95% CI: 0.06-0.58; p=0.003), less or equal to 4 antenatal care visits (OR=8.7, 95% CI: 3.19-23.80; p≤0.001) and not using postpartum contraceptives (OR=5.7, 95% CI: 1.64-19.81; p=0.006) were independently associated with short birth interval. Conclusions: The prevalence of short birth interval is still high in Uganda as compared to global report. The predictor factors of short birth interval include maternal lack of pregnancy planning, low number of antenatal care visits, breastfeeding for less than 12 months and lack of postpartum contraceptive use. Women of reproductive age should routinely be educated about child spacing by healthcare workers.